Car Free Day as an Alternative for Educational Tourism For Families in Padang City - Lili Dasa Putri (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
Excessive works and routines carried out either by children, adults, or parents can lead to boredom so that they need the means to make them fresh. Many things can be done to restore the spirit and make them refresh, starting from sports, recreation, and so on. Nowadays, car free day in several cities is getting attention in Indonesia. It is usually conducted on the weekend both in small cities and big cities. There are many things that can be done and enjoyed during the car free day, and all ages can enjoy it. A car free day can be a form of educational tourism because it provides many educational contents directly or indirectly. Besides, on the car free day, visitors can also enjoy a variety of local, national, and even international culinary delights. Besides being able to refresh, on a car free day, people can also get daily necessities because many sellers can be found there and sell various types of goods. Therefore, the car free day deserves to be an alternative for educational tourism for families.